Effectiveness of a 5-Week Virtual Reality Telerehabilitation Program for Children With Duchenne and Becker Muscular Dystrophy: Prospective Quasi-Experimental Study. - Baeza-Barragán, María Rosa; Labajos-Manzanares, María Teresa; Amaya-Álvarez, Mercedes Cristina; Morales-Vega, Fabián; Rodríguez-Ruiz, Judit; Martín-Valero, Rocío (JMIR, 2023)
Duchenne muscular dystrophy (DMD) and Becker muscular dystrophy (BMD) are neuromuscular diseases.The main objective was to test whether children with DMD and BMD obtain different results on the 6MWT after completing 10 telerehabilitation treatment sessions. The secondary objective was to measure whether other specific motor scales also produce different results after the 10 defined sessions. Methods: This was a descriptive, open, and quasi-experimental study with a prospective A-B (control-intervention) design. A sample of 12 participants who fulfilled the inclusion criteria followed the program for 5 weeks with 10 telerehabilitation sessions. During the sessions, the participants used virtual reality glasses to train for the treatment goals. Results: The participants showed a 19.55-meter increase in the 6MWT. Motor function also remained stable according to other scales used to assess it. The North Start Ambulatory Assessment scores were stable in both treatment conditions (P=.20). Furthermore, the timed up and go test results were 0.1 seconds faster in the telerehabilitation condition, and the Motor Function Measure in all of the 3 dimensions showed no significant differences (P=.08). Finally, the Effort Perception Infant scale showed that during the training, fatigue increased in the middle and decreased by the end of the sessions, but the perception throughout the sessions was lower even as the exercise intensity increased. Conclusions: There were no differences between conventional and telerehabilitation treatments, so the telerehabilitation tool could be used without harming children with DMD and BMD, facilitating their access to therapies and stimulating learning to maintain their functional capacity. Therefore, telerehabilitation in general may be helpful in maintaining motor function in children with DMD and BMD. The learning effect helped reduce the feeling of fatigue in the children during the program.
Keywords: Distrofia muscular; Duchenne, Distrofia muscular de; Fisioterapia - Innovaciones tecnológicas; Pacientes - Rehabilitación; Realidad virtual en medicina; Duchenne muscular dystrophy; Telerehabilitation; Virtual reality; Physical therapy; Muscular dystrophy; Mutation; Muscle; Degeneration; Telehealth; Motor function; Digital health intervention; Becker muscular dystrophy